2008
DOI: 10.1080/15513810802026526
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Soft Part Sarcoma: Clinical, Histopathological, Molecular, and Ultrastructural Aspects

Abstract: Alveolar soft part sarcoma (ASPS) is a rare soft tissue tumor occurring mainly in the adolescents and young adults. Multimodality treatment has not been effective, and excision remains the mainstay of treatment. Histopathologically, it varies little from case to case. It is composed of organoid aggregates of large polygonal cells with vesicular nuclei and abundant granular, eosinophilic cytoplasm, separated by delicate vascular channels. The line of differentiation of this unique tumor is yet undetermined, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As with other space-occupying lesions in the orbit, patients with ASPS primarily present with proptosis, abnormal position of the eyes, eyelid swelling, and conjunctival congestion with dilated and tortuous vessels ( 16 ). In certain cases, metastasis to the lungs or brain may be the presenting feature of ASPS ( 44 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…As with other space-occupying lesions in the orbit, patients with ASPS primarily present with proptosis, abnormal position of the eyes, eyelid swelling, and conjunctival congestion with dilated and tortuous vessels ( 16 ). In certain cases, metastasis to the lungs or brain may be the presenting feature of ASPS ( 44 ).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Typically, prominent, periodic acideSchiff (PAS) positive, diastase-resistant crystals and granules are seen. 15,16 Initial studies of these cytoplasmic granules reported protein and polysaccharide complexes. 16 Further experimentation has found an accumulation of MCT1-CD147 complexes, as CD147 has two potential TFE3 binding sites (the transcription factor which was translocated), this overproduction could be related to the novel genetic sequence of ASPS; however, further transactivation assays need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the pattern is uniform and characterized by groups or compartments of cells, these structures being separated from each other by thin-walled vascular channels and matrix septa, resulting in a (pseudo)alveolar-like image giving the tumor its name. This alveoloid pattern is furthermore promoted by loss of cell adhesion and thus gap formation caused by regressive changes commonly occurring in the center of the cellular compartments (Weiss and Goldblum 2001;Khanna et al 2008). At the periphery of the lesion, abnormal and dilated blood vessels are a typical feature, and angioinvasion is typical for this neoplasm.…”
Section: General Histologic Features Of Alveolar Soft Part Sarcomamentioning
confidence: 99%